The Phenomena of Hijrah and the Rise of Middle-Class Muslims in Banyumas: Agency, Articulation, and Domination - Juliansyahzen, Muhammad Iqbal (Indonesian Academy of Social and Religious Research (IASRR), 2024)
This study examines the religious phenomenon practised by middle-class Muslim communities in Banyumas. Middle-class Muslim society plays an essential role in social changes. Educational and economic levels and broader social networks identify these community groups. The critical question is how this community group is in its religious context. This research is a field research with a sociological approach. The researcher uses Anthony Giddens' theory to see the dynamics of religion comprehensively. The primary data comes from understanding and practising the diversity of the Muslim community itself, as well as observing three urban mosques: the MBJS Mosque, the FZ Mosque, and the MGI. The secondary data comes from bulletins, journals, books, media, etc. The research concludes that middle-class Muslims make efforts to contextualize the fundamental conception of hijrah with the reality of modern urban Muslim society. However, it is still general and symbolic. The articulation of understanding is manifested in the life of religious issues and issues such as staying away from usury, music, and so on. Understanding that tends to be textual is inseparable from the structure and agents surrounding it.